Career Plateaus Reconsidered - Feldman, Daniel C.; Weitz, Barton A. (Journal of Management, 1988)
This paper suggests that a variety of individual, job-related, and organizational factors influence whether employees reach career plateaus. The importance of examining causes of career plateaus is discussed in terms of managing career development more effectively and in terms of conducting further research in the area.